PP-27 Survey of children and young people's perceptions of clinical research. Issue 10 (20th September 2017) - Ni,; Li,; Qi,; Shu,
Abstract : Background: Both international declarations and some national legislation required that children and young people need to consent to participating a clinical re-search when they have the capacity to make their own decisions. However, the children and young people's perceptions of paediatric clinical research is unknown. Fur-thermore, it is difficult to conduct a paediatric clinical trial because of enrollment difficulties. This study was con-ducted to investigate the children and young people's perceptions of clinical trial. Methods: The survey was conducted through We-Chat investigation network aged from 8–18 years. Results: The effective questionnaires are 800 copies. Children and young people's overall awareness rate of the clinical study is 40.13%. It revealed that 21% people believed that clinical research was to treat people as ex-perimental rats. When asked 'who have the final decision on research participation'. Chose oneself, parents/guard-ian and doctor are 46.88%, 74.88% and 37% respectively. When asked 'If you want to participate a study, but your parents/guardian do not agree, what would you do?', chose give up, persuade parents agree and unknown were 35.75%, 41.00%, 19.63% respectively. When asked 'If you do not want to participate a study, but your parents/guardian thinks you should, what would you do? 'chose listen to parents, refuse the suggestions of parents/guard-ian, unknown were 56.75%, 24.13% and 15.5.0% respec-tively. When asked'If the trial is similar to the ordinary clini-cal treatment, would you agree to participate?', chose very willing, willing, neutral and unwilling was 10.88%, 40.88%, 27.75%, and 18.25% respectively. When asked 'If the clin-ical research is helpful to you, but it need to draw a little more blood, do you like to participate', chose very willing, willing, neutral and unwilling was 12.88%, 42.63%, 15.63% and 24.50%. When asked 'If the clinical research is helpful for you, but it need to add some unpainful tests, would you like to participate?', chose very willing, willing, neutral and unwilling were 10.13%, 39.63%, 24.25% and 23.50%. As to 'what are your most concerns of participate an in-vestigation?', chose 'worry about added pain or discom-fort' was 68.63%, chose'people treat me differently when they know me participate the research'was 11.13%. As to 'How can reduce your concerns or make you feel better to participate the research?', chose 'doctors and nurses take good care of me' was 64.00%, chose 'get to know more about research'was 41.88%. As to'how can encour-age you to participate an research?', chose 'know that other people also participate the research' was 58.75%, chose 'know the information after research'was 48.38%, chose 'get economy compensation' was 31.13%. When asked 'If the research is not helpful for you, but it will help others, will you participate?', chose willing and unwilling was 78.75% and 21.25% respectively. Conclusion: It is very necessary to education and cor-rect guide children and young people's understanding of clinical research. It is very necessary to concern about the children and your people who involved in the research. The situation of the paediatric clinical trial recruitment dif-ficulties could be improved by efforts.